Analysis of Polycyclic Aromatic Hydrocarbons (PAHs) in Road Runoff Water from High Traffic Area of Guwahati City, Assam, India - Dr. Yamin Hassan (International Journal of Engineering and Management Research, 2018)
Road runoff water samples were collected for the analysis of eight PAHs during first flush and aftermath in monsoon season of the year 2014-15 from 12 sites associated with high traffic activities round the clock . All the sites were selected for investigation to represent the high traffic activity areas of Guwahati city, Assam, India. Eight common environmental PAHs [Phenanthrene-(PHE), Benzo(K)FLUORANTHENE(-BKF), Benz(a) Pyrene-(BAP), Benzo(ghi)Pyrene-(BGHIP), Benzo(a) Anthracene/Chrysene-(BAA/CHR), Fluoranthene-(FLT), Pyrene-(PYR), Anthracene-(ANT)] were found to be distributed and the concentrartion of PAHs was determined by using HPLC technique. Polycyclic aromatic hydrocarbons (PAHs) are potentially mutagenic and carcinogenic substances occurring at various concentrations in atmosphere, soils, waters and sediments. PAHs, inherited both from natural and anthropogenic processes, are persistent organic pollutants (POP) due to their chemical stability and biodegradation resistance. The present data indicates that the total average of PAHs over the investigated sites was ranged from 0.005 ng/l to 0.057 ng/l. On individual scale, the highest concentration were 0.057 ng/l and 0.053 ng/l for BKF and ANT. The investigation showed the carcinogenic content of PAHs (BKF) was found in all the investigated runoff water samples. The increase of road transportation, and of industrial and activities has led to a notable build up of PAH amounts in the environmental media.